2017
DOI: 10.4103/ija.ija_317_17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy of palonosetron-dexamethasone combination with palonosetron or dexamethasone alone for prophylaxis against post-operative nausea and vomiting in patients undergoing laparoscopic cholecystectomy

Abstract: Background and Aims:Post-operative nausea and vomiting (PONV) is highly distressing and unpleasant symptom. Dexamethasone and palonosetron are effective antiemetics with minimal side effect profile. This study compares the efficacy of palonosetron or dexamethasone alone and their combination (palonosetron plus dexamethasone) for prevention of PONV after laparoscopic cholecystectomy.Methods:This prospective, randomised, double-blind trial was done on 187 adults, American Society of Anesthesiologists Grade I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The total incidence of PONV in our study was 21.25%, which is consistent with the results of other studies in the literature [3,5,[16][17][18]. During the first postoperative 24 h, the incidence of PONV was also comparable to other study results [17,19]. After 24 h, the incidence of PONV was lower in the GI group (5%) than in the GII group (12.5%), although the difference was not statistically significant (P = 0.43).…”
Section: Discussionsupporting
confidence: 92%
“…The total incidence of PONV in our study was 21.25%, which is consistent with the results of other studies in the literature [3,5,[16][17][18]. During the first postoperative 24 h, the incidence of PONV was also comparable to other study results [17,19]. After 24 h, the incidence of PONV was lower in the GI group (5%) than in the GII group (12.5%), although the difference was not statistically significant (P = 0.43).…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that palonosetron alone and a combination of palonosetron–dexamethasone were equally effective in the prevention of PONV; however, dexamethasone alone was least effective among the three groups. [ 19 20 ] The combination of palonosetron–dexamethasone was more effective as compared to only palonosetron for reducing PONV after laparoscopic cholecystectomy. [ 21 ] However, in our study, we observed that the combination of palonosetron–dexamethasone did not significantly reduce the incidence of PONV when compared with either drug alone.…”
Section: Discussionmentioning
confidence: 99%
“…Many prophylactic antiemetic agents have been recommended to minimise this postoperative side effect, a combination of dexamethasone and 5-HT 3 receptor antagonist has been suggested to prevent PONV in patients with a high risk. [ 4 ] The previous studies revealed that a combination of dexamethasone and ondansetron is more effective than ondansetron alone in reducing PONV after strabismus surgery,[ 13 14 ] our current regimen in preventing PONV includes a multimodality approach by using a combination of dexamethasone and 5-HT 3 receptor antagonist during anaesthesia induction. We found that the incidence of PONV following strabismus surgery with the combination of dexamethasone and 5-HT 3 receptor antagonist is significantly lower than that reported in previous studies,[ 12 ] this can be explained by the anaesthetic agents selected and non-use of N 2 O in our study.…”
Section: Discussionmentioning
confidence: 99%